The separation of powers in Malaysia / Ismail Bakar - Bakar, Ismail (Faculty of Law, 1987)
For the discussion of the Doctrine of Seperation of Powers, it is traceable back to Aristotle, and then it was developed by Locke and its best known formulation in its modern form by the French political philosopher, Monstesquieu. Aristotle in his 'Politics' made the first attempt to classify the organs of government " 1 1. That which deliberates about public affairs 2. That which is concerned with the Magistrates ..... and 3. That which has Judicial power". The deliberative element, which is regarded as Supreme, he defines as having authority in matters of war, peace and alliances, the passing of laws and the audit of public accounts. The second element is the system of Magistracies of distribution of offices. This covers the setting up of public offices, their authority and the manner of appointment. Aristotle is thinking here of those who have the power of deciding policy and issuing orders, especially in relation to revenue and defence. Under the Judicial part he discusses the staffling and Jurisdiction of the law courts.